Angiogenesis and Progression in Human Melanoma. (13th May 2010) - Ria, R.; Reale, A.; Castrovilli, A.; Mangialardi, G.; Dammacco, F.; Ribatti, D.; Vacca, A.
Abstract : In tumor growth, angiogenesis, the process of new-formation of blood vessels from pre-existing ones, is uncontrolled and unlimited in time. The vascular phase is characterized by the new-formation of vascular channels that enhances tumor cell proliferation, local invasion and hematogenous metastasis. Human malignant melanoma is a highly metastatic tumor with poor prognosis, and high resistance to treatment. Parallel with progression, melanoma acquires a rich vascular network, whereas an increasing number of tumor cells express the laminin receptor, which enables their adhesion to the vascular wall, favouring tumor cell extravasation and metastases. Melanoma neovascularization has been correlated with poor prognosis, overall survival, ulceration and increased rate of relapse. Secretion of various angiogenic cytokines, i.e. VEGF-A, FGF-2, PGF-1 and -2, IL-8, and TGF-1 by melanoma cells promote the angiogenic switch and has been correlated to transition from the radial to the vertical growth phase, and to the metastatic phase. Moreover, melanoma cells overexpressα vβ 3, α vβ 5, α 2β 1 andα 5β 1 integrins and release, together with stromal cells, higher amount of metalloproteases that increasing their invasive potential and angiogenesis. Basing on these observations, different molecular targets of antiangiogenic molecules has be recognized and various antiangiogenic agents are currently in preclinical and clinical trials for melanoma.